GIANT MOLECULAR CLOUDS AND MASSIVE STAR FORMATION IN THE SOUTHERN MILKY WAY - García, P.; Bronfman, L.; Nyman, Lars-Åke; Dame, T. M.; Luna, A. (The Astrophysical journal. Supplement series, 2014)
The Columbia UniversityemdashUniversidad de Chile CO Survey of the southern Milky Way is used to separate the CO(1-0) emission of the fourth Galactic quadrant within the solar circle into its dominant components, giant molecular clouds (GMCs). After the subtraction of an axisymmetric model of the CO background emission in the inner southern Galaxy, 92 GMCs are identified, and for 87 of them the twofold distance ambiguity is solved. Their total molecular mass is M(H sub(2)) = 1.14 + or - 0.05 x 10 super(8) M sub([middot in circle]), accounting for around 40% of the molecular mass estimated from an axisymmetric analysis of the H sub(2) volume density in the Galactic disk, M(H sub(2)) sub(disk) = 3.03 x 10 super(8) M sub([middot in circle]). The large-scale spiral structure in the southern Galaxy, within the solar circle, is traced by the GMCs in our catalog; three spiral arm segments, the Centaurus, Norma, and 3 kpc expanding arm, are analyzed. After fitting a logarithmic spiral arm model to the arms, tangent directions at 310[degrees], 330[degrees], and 338[degrees], respectively, are found, consistent with previous values from the literature. A complete CS(2-1) survey toward IRAS point-like sources with far-IR colors characteristic of ultracompact H II regions is used to estimate the massive star formation rate per unit H sub(2) mass (MSFR) and the massive star formation efficiency ( epsilon ) for GMCs. The average MSFR for GMCs is 0.41 + or - 0.06 L sub([middot in circle])/M sub([middot in circle]), and for the most massive clouds in the Norma arm it is 0.58 + or - 0.09 L sub([middot in circle])/M sub([middot in circle]). Massive star formation efficiencies of GMCs are, on average, 3% of their available molecular mass.